Too Complex to Digest? Federal Tax Bills and Their Processing in US Financial Markets - Hamza Bennani; Matthias Neuenkirch (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this paper, we analyze whether the complexity of tax bills affects financial markets. Based on the Flesch-Kincaid grade level of the 32 tax bills identified by Romer and Romer (2010) in the period 1962–2003, we assess the relationship between tax bills' complexity and financial markets using an event study approach. Our results show a negative (positive) and significant relationship between the present value of tax bills and changes in the 10-year government bond yields (S&P 500 returns). The magnitude of this relationship increases over time, suggesting that market participants underreact at first and need a couple of days to digest the information contained in the tax bills. This delay can be explained by the textual characteristics of the bills in the case of the 10-year yields as a lower readability partly offsets the negative relationship for up to three days after the signing of a tax bill, but not thereafter. In the case of the stock market, we find similar offsetting evidence, but only for a part of the readability measures employed in this paper.
Keywords: G14; H20; H30; 330; complexity; event study; financial markets; readability; tax bills